DIAGNOSTICS AND TREATMENT OF CONGENITAL MALFORMATIONS OF THE LUNG AND MEDIASTINUM IN NEWBORN CHILDREN AND INFANTS - S. A. Karavaeva; T. K. Nemilova; A. N. Kotin; T. V. Patrikeeva; S. V. Starevskaya; N. A. Il’Ina; N. A. Borisova (Вестник хирургии имени И.И. Грекова)
The article presents the experience of treatment of newborn children and infants with congenital malformations of the lung and mediastinum, which required a surgery. Children (138 cases) were treated during recent 18 years. There was a prevalence of full-term infants (73%). Fetal malformations were diagnosed in prenatal period in majority of cases. Computed tomography was the main method of diagnostics after delivery. Children (110 cases) were operated out of 138. Children with extrapulmonary sequestration didn’t undergo surgery in case of absence of clinical manifestations. The authors made a conclusion that malformations of the lung and mediastinum should be included in number of differentiated diseases in case of respiratory distress syndrome in newborn children. The indications to early surgery should be the danger of contamination and malignant transformation, presence of intrathoracic tension syndrome in neonatal period.